2013
DOI: 10.4236/jsemat.2013.34038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Content on Ti Inclusion Precipitated in Tire Cord Steel

Abstract: The precipitation of TiN inclusion during solidification of different carbon content of 0.72%, 0.82% and 0.95% in tire cord steel is thermodynamically studied respectively. The results show that the carbon content has obvious effect on TiN inclusion precipitated in tire cord steel of different strength levels. With the carbon content of tire cord steel increasing, the temperature before solidifying reduced gradually and the required activity product of titanium and nitrogen for TiN inclusion precipitation also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It is stated in many papers [18][19][20][21][22][23][24] that chemical composition, pollution of steel by non-metallic inclusions, results of liquation processes, presence of scale on the surface of rod and its decarburization, and the peculiarities of macro and microstructure have a great influence on the processability of steel rod in the following operations of technology: rough drawing, patenting, drawing of brass-plated wire, and laying, as well as the quality of the final product.…”
Section: Steel Rod For High-strength Wire Manufacturingmentioning
confidence: 99%
“…It is stated in many papers [18][19][20][21][22][23][24] that chemical composition, pollution of steel by non-metallic inclusions, results of liquation processes, presence of scale on the surface of rod and its decarburization, and the peculiarities of macro and microstructure have a great influence on the processability of steel rod in the following operations of technology: rough drawing, patenting, drawing of brass-plated wire, and laying, as well as the quality of the final product.…”
Section: Steel Rod For High-strength Wire Manufacturingmentioning
confidence: 99%
“…The main types of tire cord steel were SWRH 62A and SWRH 67A (about 1750 MPa) before the 1990s, and then after that SWRH 72A (about 1870 MPa). In the 21st century, the hypereutectoid tire cord steel (SWRH 82A) dominated the market due to its higher strength level [2,3]. Nowadays, the research on ultra-high strength level steel, such as SWRH 92A tire cord steel, has been drawing the increasing attention of manufacturing engineers.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers [2][3][4][9][10][11][12][13][14] have reported the precipitation behaviors of TiN inclusion in different types of steels over the decades. Jiang et al [4] found that the solidification segregation ratio of Ti was far greater than that of N, and reported that TiN inclusion would not precipitate until the solid fraction reached 0.9 when using SWRH 82A tire cord steel.…”
Section: Introductionmentioning
confidence: 99%